ANALYSIS AND DESIGN OF DIGITAL COMIC BASED ON EDUCATION IN OVERCOMING GLOBAL WARMING IN INDONESIA - Deli Deli; Hery Yanto (Universitas Internasional Batam, 2022)
At present, information regarding global warming is usually offered in the form of written information or posters that can be read at a glance, with the hope that people will be interested in exploring the issue further. The importance of global warming can be conveyed effectively and interestingly through the digital comic. On the topic of global warming, digital comic can be a great way to communicate the subject. A comic can trigger certain affective processes and responses to readers. This makes it suitable for telling complex and emotionally rich stories without requiring one to read long or complicated texts. The availability of modern and digital information media makes it possible for humans to access and know about information more readily and more effectively. This research uses the ADDIE method in designing digital comic about global warming. The result of this research is an educational-based digital comic that provides material about global warming in Indonesia.